A hybrid precoding‐ and filtering‐based uplink MC‐LNOMA scheme for 5G cellular networks with reduced PAPR. Issue 10 (14th August 2018) - Baig, Imran; Farooq, Umer; Ahmed, Ejaz; Imran, Muhammad; Shoaib, Muhammad
Abstract: Uplink multicarrier localized nonorthogonal multiple access (MC‐LNOMA) is a variant of hybrid nonorthogonal multiple access, where subcarrier mapping is performed in localized mode. MC‐LNOMA is one of the most prominent emerging schemes and likely to be employed in the forthcoming fifth‐generation cellular networks due to its massive connectivity, spectral efficiency, better cell coverage capability, and higher data rate. It may employ orthogonal frequency‐division multiple access due to the technical ripeness. However, schemes based on orthogonal frequency‐division multiple access all suffer from the high peak‐to‐average power ratio problem. Therefore, in this paper, a new finite impulse response filter–based discrete cosine transform–precoded uplink MC‐LNOMA scheme is presented for peak‐to‐average power ratio reduction. MATLAB simulations demonstrate the performance supremacy of the proposed scheme compared to contemporary schemes such as discrete cosine transform–precoded uplink MC‐LNOMA and nonprecoded uplink MC‐LNOMA. Abstract : 1. To cope with the problem of high Peak‐to‐Average Power Ratio (PAPR), a new finite impulse response filter based Discrete Cosine Transform (DCT) precoded uplink Multicarrier Localized Non‐Orthogonal Multiple Access (MC‐LNOMA) scheme is presented. 2. In the proposed scheme, the coefficients of the FIR filter (discrete‐time impulse response) are multiplied with the DCT‐precoded modulated data to reduce the PAPR.